2014
DOI: 10.3389/fnhum.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Habenular expression of rare missense variants of the β4 nicotinic receptor subunit alters nicotine consumption

Abstract: The CHRNA5-CHRNA3-CHRNB4 gene cluster, encoding the α5, α3, and β4 nicotinic acetylcholine receptor (nAChR) subunits, has been linked to nicotine dependence. The habenulo-interpeduncular (Hb-IPN) tract is particularly enriched in α3β4 nAChRs. We recently showed that modulation of these receptors in the medial habenula (MHb) in mice altered nicotine consumption. Given that β4 is rate-limiting for receptor activity and that single nucleotide polymorphisms (SNPs) in CHRNB4 have been linked to altered risk of nico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
1
39
0
Order By: Relevance
“…The role of β4* nAChRs has been investigated in certain nicotine-mediated behaviors, including nicotine-elicited seizures (Salas et al, 2004), aversion (Frahm et al, 2013;Slimak et al, 2014), anxiety (Salas et al, 2003), and withdrawal (Salas et al, 2004;Zhao-Shea et al, 2013), supporting the involvement of this subunit in regulating the aversive properties of nicotine (Fowler and Kenny, 2014). However, recent findings provide evidence for their role in the habenulo-interpeduncular pathway in nicotine reinforcement.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The role of β4* nAChRs has been investigated in certain nicotine-mediated behaviors, including nicotine-elicited seizures (Salas et al, 2004), aversion (Frahm et al, 2013;Slimak et al, 2014), anxiety (Salas et al, 2003), and withdrawal (Salas et al, 2004;Zhao-Shea et al, 2013), supporting the involvement of this subunit in regulating the aversive properties of nicotine (Fowler and Kenny, 2014). However, recent findings provide evidence for their role in the habenulo-interpeduncular pathway in nicotine reinforcement.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, variants in the β4 regulatory domain reduce the age of tobacco initiation, while gain-offunction variants in CHRNB4 reduce the risk of nicotine dependence (Haller et al, 2012;Saccone et al, 2009;Schlaepfer et al, 2008). Although cholinergic responses are unaffected in CHRNB4 coding variants, nicotine-elicited currents are increased (Haller et al, 2012), which is reflected as aberrant nicotine aversion in mice expressing these variants (Slimak et al, 2014), and as fewer cigarettes smoked per day in humans (Haller et al, 2012). These studies have shown that the β4-containing (β4*) subpopulation of nAChRs merits further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…A number of SNPs have been found in the b4 subunit gene associated with cigarette consumption in human and the injection of lentiviruses carrying the wild-type b4 subunit or these b4 variants in the MHb of mice leads to aversion or preference for nicotine depending on whether the variants increase or decrease nicotine currents (Slimak et al, 2014).…”
Section: Recent Electrophysiological and Pharmacological Studies Havementioning
confidence: 99%
“…In mice chronically treated with nicotine, null mutations of the a2 and a5 subunits highly expressed in the IPN reduced mecamylamine-induced withdrawal, and in wild-type mice microinfusion of mecamylamine into the Hb or IPN precipitated withdrawal (Salas et al, 2009). Moreover, lentiviral expression in the MHb of a gain-of-function Thr374Ile variant of the b4 nAChR subunit associated with reduced risk of smoking resulted in strong nicotine aversion in mice, whereas expression of a loss-of-function Arg348Cys variant failed to induce nicotine aversion (Slimak et al, 2014). Nicotine-induced excitation of the MHb neurons in mice was mediated by tachykinin NK 1 and NK 3 receptors (Dao et al, 2014).…”
Section: Nicotinementioning
confidence: 99%